RESPON VARIETAS KEDELAI (Glycine max L. Merr) PADA TINGKAT KELENGASAN TANAH YANG BERBEDA - Aminah Aminah; Nirwana Nirwana; Marlina S. Palad (Percetakan Umi Toaha Makassar, 2017)
The growth ofsoybean in wet land and dry land not always supported by optimal soil moisture conditions to high level production. In the wet field saturated soil often found in the lower area until remain water irrigation cannot wasted to lower area. Once effort of soybean cultivation in the saturated soil used variety which tolerance in saturated soil.The experiment was conducted in a glasshouse at BALITSEREAL Maros, from May 2013 until Sep 2013. A completely randomized design 4 x 4 factorial arrangement with three replication was used. The first factor is level soil moisture content, field capacity, 5% above field capacity, 15% above field capacity, 25% above field capacity, and the second factor is soybean varieties Wilis, Sinabung, Kaba and Dieng.Result showed there is no interactionbetweensoil moisture content and varieties to number of pods and seed weight. Interaction caused treatment occurred to number of leaf, leaf area, total dry matter, dry weight nodules, crop growth rate, net assimilation rate, spesific leaf area, and leaf area ratio. Treatment of soil moisture content which 5% and 15% above field capacity showed higher productivity than soil moisture content 25% above field capacity. Varieties Sinabung and Kaba showed higher productivity than varieties Wilis and Dien.